ANALISA TERHADAP FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENERAPAN MOBILE BANKING - Hendi Prihanto; Rika Yuniati (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2021)
This research was conducted with the aim to assess empirically the effect of information systems, knowledge and dissemination of the effectiveness of the implementation of mobile banking. Criteria standard sample of 100 respondent, this kind of research is done using primary data. The study was conducted with the object of study is a customer of Bank Central Asia branch of Gajah Mada. The data collection was done by direct the respondent to come to Bank Central Asia branch of Gajah Mada. This study used quantitative research methods. Researchers using multiple linear regression analysis using SPSS 22. Results of research has been done on the system and the knowledge and dissemination of information on the effectiveness of the application of mobile banking at Bank Central Asia branch of Gajah Mada. Shows that the effect of information systems, knowledge and socialization positive influence on the effectiveness of the mobile banking application.